2011
DOI: 10.1007/s00464-011-1656-7
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, simulation-based skills training collaborative using shared GI mentor II systems: results from the Texas association of surgical skills laboratories (TASSL) flexible endoscopy curriculum

Abstract: The feasibility of sharing educational and training resources among institutions was demonstrated. Likewise, the concept of "mobile simulation" appears to be useful and effective, with three of the four institutions involved successfully in implementing the training curriculum during a fixed period. Additionally, subjects who completed the training demonstrated both subjective and objective improvements in flexible endoscopy skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…34 Study participants showed significant improvements in objective flexible endoscopy skills, and the curriculum was found to be educationally useful and effective. Gomez and colleagues 14 used this curriculum with the addition of practice on 10 colon cases on the GI Mentor II simulator to show that flexible endoscopy skills transferred to the clinical environment.…”
Section: Endoscopic Skillsmentioning
confidence: 97%
See 2 more Smart Citations
“…34 Study participants showed significant improvements in objective flexible endoscopy skills, and the curriculum was found to be educationally useful and effective. Gomez and colleagues 14 used this curriculum with the addition of practice on 10 colon cases on the GI Mentor II simulator to show that flexible endoscopy skills transferred to the clinical environment.…”
Section: Endoscopic Skillsmentioning
confidence: 97%
“…Previous research comparing time-, repetition-, and proficiency-based training protocols has shown that learners who practice according to the proficiency-based protocol achieve higher levels of performance with little variability among trainees, even when total training time and repetitions are held constant among these training protocols. 30 Proficiency metrics have been established and validated for many surgical tasks, such as knot tying and suturing, 31,32 laparoscopic skills, 33 and endoscopic skills, 34 and continue to add to the growing body of data supporting the use of simulationbased training in GME.…”
Section: Technical Skillsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shirai et al [59] 2008 20 residents OGD 11 items 5-grade scale Van Sickle et al [60] 2011 41 trainees Colonoscopy GI Mentor Ⅱ and GAGES OGD: Oesophago-gastro-duodenoscopy; GI: Gastrointestinal; PEG: Percutaneous Endoscopic Gastroscopy; GAGES: Global Assessment of Gastrointestinal Endoscopic Skills.…”
Section: Station-specific Checklist and Global Scorementioning
confidence: 99%
“…Only 1 study [50] assessed trainees' performances using multimodal assessment tools which were OSATS, ICSAD and final product analysis (FPA) (leakage and permeability of an anastomosis). In another study [60] , endoscopic skills were assessed by a combination of the simulator-based scores and Global Assessment of Gastrointestinal Endoscopic Skills (GAGES) scores. Two studies developed intensive boot camp session for new residents in order to boost their basic technical skills at the start of their training programme [52,54] .…”
Section: Table 5 Characteristics Of Studies Integrating Skills Assessmentioning
confidence: 99%